Early medieval habitat and burials (6th-9th century) of Soulages (Saint-Maurice-Navacelles, Hérault) [abridged version] - Agnès Bergeret; Guergana Guionova; Richard Donat; Vivien Vassal; Isabel Figueiral; Vianney Forest; Laurent Bruxelles; Frédéric Chandevau; Yves Manniez; Isabelle Commandré; Bernard Gratuze; Frédéric Raynaud (Archéologie Médiévale)
Located on the plateau of Larzac, the site of Soulages testifies, for the first time in a low mountain area, a rural settlement which expand from the 6th to the 9th century. The remains are organised in an area that groups together all living quarters, mixed with the burials of the inhabitants. Within this area, the buildings are divided by activity: the service buildings are gathered in areas surrounded by a palisade, the main house is secluded above them. In addition to the locations of the buildings, the study of the construction techniques and materials also makes it possible to distinguish the main dwelling house from the service buildings, with the use of stone for the former and the use of wooden load-bearing structures and earthen walls for the latter. Among the burials, young children are over-represented. This kind of settlement yields few material remains documenting the life of a community settled ex nihilo.